Effect of Chitosan, Chitosan Nanoparticle, Anacyclus pyrethrumand Cyperus rotundusin Combating Plasmid Mediated Resistance in Periodontitis - Subbiah, Usha; Elayaperumal, Gokulalakshmi; Elango, Sonaa; Ramanathan, Arvind; Gita, Bagavad; Subramani, Karthikeyan (Anti-Infective Agents, 2020)
Background: Chitosan, chitosan nanoparticle, ethanolic extracts of Anacyclus pyrethrum root and Cyperus rotundus rhizome were evaluated against plasmid mediated multidrug resistance of Enterococcus faecalis, Staphylococcus aureus and Bacillus sp. isolated from unstimulated saliva of chronic periodontitis. The main aim of the current study centres the reduction of antibiotic consumption and the development of natural compounds to combat multidrug resistance. Methods: Identification of bacteria, antimicrobial susceptibility, plasmid stability and plasmid curing was carried out for the characterization of resistance plasmids. Results: E. faecalis showed 89% of sensitivity to chitosan nanoparticle, chitosan 81%, C. Rotundus 69% and A. pyrethrum 62% for S. aureus, with the MIC >100 μg/ml. In comparison with the antimicrobials tested, maximum resistance to tetracycline (89%) for E. faecalis, is followed by ampicillin (87%) and tetracycline (81%) for S. aureus. Meanwhile, chloramphenicol and tetracycline (80%) for Bacillus sp. The plasmid stability for E. faecalis (20%), S. aureus (<4%) and Bacillus sp. (16%). The order of stability corresponding to the broth media is LB > BHI > nutrient for E. faecalis, S. aureus but similar in LB and nutrient broth for bacillus sp. The maximum plasmid curing efficiency of chitosan for S. aureus (76%), Chitosan nanoparticle for E. faecalis (88%), A. pyrethrum for S. aureus (73%), C. rotundus for E. faecalis (87%). The order of plasmid curing efficiency is chitosan nanoparticle>C. rotundus>chitosan>A. pyrethrum. Conclusion: Chitosan, Chitosan nanoparticle, C. rotundus, and A. pyrethrum offered a greater potential in eliminating plasmid mediated resistance acquired by periodontal pathogens, thus addressing this crisis in dentistry.
Keywords: Chitosan